THE FUNCTIONS OF POLITICIANS’ SPEECH ACTS IN THE ELECTION CAMPAIGN FOR MAYOR AND DEPUTY MAYOR OF TOMOHON CITY: FUNGSI TINDAK UCAPAN POLITIKUS DALAM KAMPANYE PEMILU UNTUK MAYOR DAN WAKIL WALIKOTA TOMOHON CITY - Yoppie A. T. Pangemanan; James Edward Lalira; Jane Elvira Scipio; Vivi Nancy Tumuju (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
This research aims to describe the assertive and commissive functions of politician speech acts in the election campaign for mayor and deputy mayor of Tomohon city. This research is a qualitative descriptive with content analysis study. Primary data was taken by recording politicians’ speeches during the campaign. The recording was then transcribed and analyzed. This study is based on speech act theory by Searle. The research findings show that the assertive and commissive functions have several subfunctions. Those were claiming, stating, suggesting, acknowledging, convincing, ensuring, supporting and supposing for assertive function and promising, giving hope, threatening and praying for commissive function. It can be recommended that the result of this study can be used by political parties in the context of their participation in the political contestation, including regional head election